Social inheritance can explain the structure of animal social networks - Amiyaal Ilany (Nature Portfolio, 2016)
Social networks have important implications to a variety of ecological and evolutionary processes. Here, Ilany and Akçay develop a social network model and show that inheritance of social contacts leads to networks with properties observed in species such as sleepy lizards and spotted hyenas.